2022
DOI: 10.3389/fpls.2022.860577
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omics Analysis Reveals That SlERF.D6 Synergistically Regulates SGAs and Fruit Development

Abstract: Steroidal glycoalkaloids (SGAs) are cholesterol-derived molecules that contribute to the pathogen defense in tomato but are toxic and considered to be antinutritional compounds to humans. APETALA2/Ethylene Responsive Factor (AP2/ERF) family transcription factors (TFs) play an indispensable role in various biological processes, such as plant growth and development, fruit ripening, biotic and abiotic stresses responses, and SGA biosynthesis. In this study, we identified 176 AP2/ERF genes that were domesticated o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…GAME genes responsible for SGA biosynthesis and regulation were also found near two major signals on chromosomes 1 and 7, including GAME1, GAME2, GAME6, GAME11, GAME17, GAME18, and GAME9. Phylogenetic analysis showed that SlERF.H6 belongs to the DREB (dehydration-responsive element binding) subfamily of ERFs, which is different from the reported ERF subfamily that regulates the biosynthesis of distinct alkaloid classes (Shoji & Yuan, 2021;Guo et al, 2022;Fig. 1b).…”
Section: Resultsmentioning
confidence: 70%
See 3 more Smart Citations
“…GAME genes responsible for SGA biosynthesis and regulation were also found near two major signals on chromosomes 1 and 7, including GAME1, GAME2, GAME6, GAME11, GAME17, GAME18, and GAME9. Phylogenetic analysis showed that SlERF.H6 belongs to the DREB (dehydration-responsive element binding) subfamily of ERFs, which is different from the reported ERF subfamily that regulates the biosynthesis of distinct alkaloid classes (Shoji & Yuan, 2021;Guo et al, 2022;Fig. 1b).…”
Section: Resultsmentioning
confidence: 70%
“…Phylogenetic analysis showed that SlERF.H6 belongs to the DREB (dehydration‐responsive element binding) subfamily of ERFs, which is different from the reported ERF subfamily that regulates the biosynthesis of distinct alkaloid classes (Shoji & Yuan, 2021; Guo et al ., 2022; Fig. 1b).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Furthermore, SlGAME9 co-binds with the SlMYC2 transcription factor to also regulate SGA biosynthesis genes [ 13 ]. In addition, SlERF.D6 can not only promote fruit ripening as AP2/ERF family transcription factors but also regulate the expression of genes in several SGAs synthesis pathways [ 37 ]. In this study, we identified a SlDOG1-like protein using GWAS and mGWAS.…”
Section: Discussionmentioning
confidence: 99%